2021
DOI: 10.3389/fpsyg.2021.618362
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Physical Activity eHealth in COVID-19 Pandemic: A Cross-Sectional Study of Effects on Motivations, Behavior Change Mechanisms, and Behavior

Abstract: ObjectivesThe aims of this research were (1) to compare the levels of physical activity of eHealth users and non-users, (2) to determine the effects of these technologies on motivations, and (3) to establish the relationship that could exist between psychological constructs and physical activity behaviors.MethodsThis cross-sectional study involved 569 adults who responded to an online questionnaire during confinement in France. The questions assessed demographics, usage of eHealth for exercise and physical act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 79 publications
5
28
0
3
Order By: Relevance
“…The results identified that only 30% of participants had METs-min/week from vigorous activity. Our findings were parallel to a study conducted in France in which there were differences in levels of vigorous activities during the COVID-19 pandemic (Marchant et al, 2021). However, the findings contraindicated the results of the previous study showing the negative effect of home quarantine on physical activity among adults in Saudi Arabia (Alfawaz et al, 2021).…”
Section: Discussionsupporting
confidence: 73%
“…The results identified that only 30% of participants had METs-min/week from vigorous activity. Our findings were parallel to a study conducted in France in which there were differences in levels of vigorous activities during the COVID-19 pandemic (Marchant et al, 2021). However, the findings contraindicated the results of the previous study showing the negative effect of home quarantine on physical activity among adults in Saudi Arabia (Alfawaz et al, 2021).…”
Section: Discussionsupporting
confidence: 73%
“…41 Many kinds of researches indicated that college student's physical activities were reduced during the lockdown period. [42][43][44][45][46] In the present study, the mean and SD of sedentary time (minutes) used daily by the students were 448.7± 73.6 and 517.8 ± 83.03 before and during lockdown respectively, which was significant (p=0.0001). GPAQ score (MET-min/week) was 1116.5 ± 125.3 before lockdown and 1149.2 ± 120.08 during the lockdown, which was also significant (p=0.0001).…”
supporting
confidence: 43%
“…Future sports activities can benefit from the solutions offered by Information and Communications Technology (ICT), such as home-based training and fitness apps (Ammar et al, 2020b). For instance, a study showed that participants who were users of eHealth for exercise and physical activity presented significantly higher levels of vigorous physical activity and total physical activity per week than non-users during the COVID-19 pandemic (Marchant et al, 2021).…”
Section: Discussionmentioning
confidence: 99%